A Moveable Feast - Hemingway, Ernest, 1899-1961. (New York : Scribner, 2003)
Published posthumously in 1964, A Moveable Feast is Ernest Hemingway's memoir of Paris in the 1920s. It is filled with portraits of other expatriate luminaries such as F. Scott Fitzgerald and Gertrude Stein; tender memories of his first wife, Hadley; and insightful recollections of his own early experiments with his craft.
Keywords: Hemingway, Ernest, -- 1899-1961 -- Homes and haunts -- France; Americans -- History -- 20th century -- France; Authors, American -- Biography -- 20th century; Paris (France) -- Intellectual life -- 20th century; Paris (France) -- Social life and customs -- 20th century